Task scheduling algorithm using grey wolf optimization technique in cloud computing environment - Khaleelahmed, Shaik; Selvaraj, Sivakumar; Mohite, Rajendra B.; Bangare, Manoj L.; Bangare, Pushpa M.; Kulkarni, Shriram S.; Ajibade, Samuel-Soma M.; Raghuvanshi, Abhishek (Institute of Advanced Engineering and Science, 2025)
Scheduling refers to the process of allocating cloud resources to several users according to a schedule that has been established in advance. It is not possible to get acceptable performance in settings that are distributed without proper planning for simultaneous processes. When developing productive schedules in the cloud, it is necessary for work scheduling to take a variety of constraints and goals into consideration.When dealing with activities that have performance optimization limits, resource allocation is a very important aspect to consider. When it comes to cloud computing, the only way to achieve great performance, high profits, high scalability, efficient provisioning, and cost savings is with an exceptional task scheduling system. This article presents a grey wolf optimization (GWO) based framework for efficient task scheduling in cloud computing environment. The proposed algorithm is compared with particle swarm optimization (PSO) and flower pollination algorithm (FPA) and GWO is performing task scheduling in less execution time and cost in comparison with PSO and FPA techniques. Execution time taken by GWO to finish 200 task in 120.2 ms. It is less than the time taken by PSO and FPA algorithm to finish same number of tasks.